KUALITAS PENGUNGKAPAN EMISI KARBON PADA LAPORAN KEBERLANJUTAN PERUSAHAAN YANG TERDAFTAR BERDASARKAN INDEKS SRI-KEHATI PERIODE 2018 – 2022 - Ovina, Maria Ellita; Meiden, Carmel (Jurnal Akuntansi, 2024)
Climate change is one of the environmental problems that is currently being considered by stakeholders, including various organizations concerned with environmental issues. The Carbon Disclosure Project (CDP) is a non-profit organization in 2000 that focuses on addressing environmental issues. CDP works by publishing an information sheet which is useful as a guide for companies to disclose greenhouse gas (GHG) emissions due to the company's business activities. The company discloses carbon emissions in its sustainability report. This research was conducted by giving a score of disclosure of carbon emissions, both quantitatively and qualitatively. Of the 5 issuers studied during the 2018-2022 period, it was found that Bank Rakyat Indonesia (Persero) Tbk. has the highest level of conformity and quality of disclosure. Quantitatively, the climate change category has high disclosure quality. Qualitatively, the energy consumption category has the highest disclosure quality. The banking sector is ranked highest in terms of quantitative disclosure of carbon emissions, while the infrastructure sector is ranked highest qualitatively.